P58 IMMEDIATE CORONARY ANGIOGRAPHY AND SYSTEMATIC TARGETED TEMPERATURE MANAGEMENT ARE ASSOCIATED WITH IMPROVED OUTCOME IN COMATOSE SURVIVORS OF CARDIAC ARREST. (18th May 2022) - Dall'Ara, G; Compagnone, M; Spartà, D; Carletti, R; Grotti, S; Guerrieri, G; Gaetani, S; Cortigiani, M; Maitan, S; Fabbri, A; Ottani, F; Caravita, L; et al.
Abstract: Background: Rapid and systematic access to coronary angiography (CAG) and target temperature management (TTM) might improve outcome in comatose patients who survive cardiac arrest (CA). However, there is controversy around indicating immediate CAG in the absence of transmural ischemia on the electrocardiogram after return of spontaneous circulation (ROSC). We evaluated the short– and long–term outcome of our retrospective cohort of patients undergoing systematic CAG and TTM, based on whether culprit lesion percutaneous coronary intervention (PCI) was performed. Methods: All consecutive comatose CA survivors with no obvious extracardiac causes undergoing TTM were included. Analysis involved the entire population and subgroups, namely patients with initial unshockable rhythm, no ST–elevation on electrocardiogram, and good neurological recovery. Results: We enrolled 107 patients with a median age of 64.9 (57.7–73.6) years. The initial rhythm was shockable in 83 (77.6%). Sixty–six (61.7%) patients underwent PCI. In–hospital survival was 71%. It was 78.8% and 58.5% in those undergoing or not PCI (p = 0.022), respectively. Age, time from CA to ROSC and culprit lesion PCI were independent predictors of in–hospital survival. Long–term survival was significantly higher in patients who underwent PCI (respectively 61.5% vs 34.1%; Log–rank: p = 0.002). Revascularization was associated with better outcomes regardless of initial rhythm (shockable vs non–shockable) and ST–deviation (elevation vs no–elevation), and improved the long–term survival of patients discharged with good neurological recovery. Conclusion: Systematic CAG and revascularization, when indicated, were associated with higher survival in comatose patients undergoing TTM, regardless of initial rhythm and ST–deviation in the post–ROSC electrocardiogram. The benefit was sustained at long–term particularly in those with neurological recovery.